Bactericidal efficacies of nebulized non-thermal atmospheric plasma-treated liquids - Ercan, Utku Kursat; Ibis, Fatma (The European Research Journal, 2017)
Objectives. Antimicrobial activities of non-thermal atmospheric plasma-treated liquids on various bacterial and fungal strains in their planktonic and biofilm forms have been widely reported. Since most of the plasma-treated liquids are water based, they might be washed off certain surfaces and they cannot be applied for the infections of respiratory tract. In the present study we have tested antimicrobial activities of plasma-treated N-acetyl cysteine solution (NAC), phosphate buffered saline (PBS) solution and deionized water when nebulized over planktonic forms of E. coli and S. aureus.Methods. Antimicrobial activities of nebulized plasma-treated liquids were evaluated with zone of inhibition test and colony counting assay. Moreover pH of NAC, PBS solution and deionized water were measured before, after plasma treatment and during nebulization since low pH is well known consequence observed in plasma-treated liquids. Results. Our results have revealed that pH of plasma-treated NAC, PBS solution and DIW decreases after plasma treatment consistent with previous reports and does not change during nebulization. Moreover, antimicrobial activity assessment indicates that nebulized plasma-treated NAC shows the strongest antimicrobial activity, which leads complete inactivation of bacteria for 103 to 106 CFU/ml initial bacterial load and 5-log reduction for 107 CFU/ml initial bacterial load on both E. coli and S. aureus.Conclusions. Plasma-treated liquids could retain their antimicrobial activity during nebulization and nebulization could be considered as a future alternative method for delivery of plasma-treated liquids for respiratory tract infections.